Efficacy of gamma-knife surgery for treating meningiomas that involve the superior sagittal sinus - (:unkn) unknown (GEORG THIEME VERLAG KG, 2007)
Background: Meningiomas involving the superior sagittal sinus (SSS) are among the most challenging tumors to treat. Authors of some recent series have advocated total removal with SSS reconstruction. However gamma-knife surgery is a reasonable choice for these tumors. Patients: This study focused on 43 cases of meningioma invading the SSS that were treated with gamma-knife therapy. Twenty-eight patients had undergone previous resection. The follow-up period after radiosurgery ranged from 24 to 86 months (median, 46 months). The median marginal dose was 15 Gy. Results: During follow-up, 22 (51%) tumors decreased in size, 16 (37%) remained unchanged, and 5 (12%) expanded. The overall rate of tumor control with radiosurgery was 89%. Conclusion: When a small meningioma involves the SSS and the sinus is patent, the first-line treatment should be radiosurgery. If the tumor is large and the sinus is patent, we recommend gross total resection with no removal of SSS. If postoperative or follow-up MR imaging demonstrates residual tumor or recurrence, gamma-knife surgery should be performed. If a large meningioma has completely obliterated the SSS, our policy is to remove the tumor and all sinus tissue without reconstructing the SSS.
Keywords: gamma knife; meningioma; radiosurgery; sinus repair; superior sagittal sinus; surgery; PARASAGITTAL MENINGIOMAS; RESECTION; RADIOSURGERY